Pengaruh Net Income, Perputaran Total Aktiva Dan Leverage Terhadap Financial Distress Padaperusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Fachrudin, Khaira Rizfia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine whether net income has an effect on financial distress in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 period, to determine whether total asset turnover has an effect on financial distress in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 period, to determine whether leverage has an effect on financial distress in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 period, to determine whether net income, total asset turnover and leverage have an effect on financial distress in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2024 period. This research uses quantitative research. The results of the analysis provide the equation Financial Distress = -3.324 + 0.180 Net Income + 0.594 Total Asset Turnover - 0.729 Leverage + e. The results of the research analysis show that net income has a significant effect on financial distress based on the results of partial hypothesis testing, namely t count (4.402) t table (1.998971) and a significant value (0.000) 0.05, meaning H1 is accepted. The results of the research analysis show that total asset turnover has a significant effect on financial distress based on the results of partial hypothesis testing, namely t count (3.387) t table (1.998971) and a significant value (0.001) 0.05, meaning H2 is accepted. The results of the research analysis show that leverage has no effect but is significant on financial distress based on the results of partial hypothesis testing, namely t count (-6.559) t table (1.998971) and a significant value (0.000) 0.05, meaning H3 is accepted. The results of the research analysis show that net income, total asset turnover and leverage have a significant effect on financial distress based on the results of simultaneous hypothesis testing, namely F count (24.554) F table (2.76) and a significant value (0.000) 0.05, meaning H4 is accepted. The results of this study are supported by the adjusted R square value of 52.5%, while the remaining 47.5% of the financial distress variable can be explained by other variables such as current ratio and corporate governance.